EDUCATION FINANCING AND GROWTH USING AN OVERLAPPING GENERATIONS MODEL: A THEORETICAL PERSPECTIVE - Ayed Zambaa, Alleiddine; Ben Hassen, Lobna (Economic Annals, 2013)
This paper proposes an overlapping generations model along the lines of the papers by Glomm and Ravikumar (1997). Its aim is to provide a theoretical extension in which we establish, in an original framework, a comparison of public and private educational financing systems in terms of economic growth. The results provide a critique of the literature that suggests that private expenditure will inevitably lead to greater economic growth than a policy of public education.